Developing Students' Worksheets of Narrative Text Using Storyboard in Teaching Writing Skill to 8th Grade Students of Junior High School - Hanifah Nurul Azijah; Anita Anggraeni Anggraeni; Ratih Inayah (PROJECT (Professional Journal of English Education), 2026)
Writing narrative text remains a persistent challenge for Indonesian EFL learners at the junior high school level, particularly in generating ideas, organizing story elements, and maintaining coherence. Despite growing interest in worksheet-based learning materials, few studies have developed structured worksheets that integrate visual media, such as a storyboard, to scaffold the writing process. This study aimed to develop a storyboard-based worksheet, assess its feasibility, and evaluate teacher and student responses toward the product. This study employed a Research and Development (R&D) design following the Borg and Gall model, involving needs analysis, product development, expert validation, and two stages of field testing with 32 eighth-grade students at SMP Negeri 3 Parongpong, West Java, Indonesia. The product was validated as feasible (75%) and received positive responses from both students and teachers across testing stages. The findings indicate that the developed worksheet is a practical instructional tool that supports students’ pre-writing process by helping them visualize story sequences and organize narrative structures. This study contributes to EFL instructional material development by demonstrating that integrating a storyboard into structured worksheets can enhance student-centered learning in narrative writing.